Quality of life in hand eczema questionnaire: Validation of the Japanese version of a disease-specific measure of quality of life for hand eczema patients - Minamoto, Keiko; Diepgen, Thomas L.; Sato, Keiko; Noguchi, Hiromitsu; Yamashita, Naoko; Yoshimura, Kazuko; Ofenloch, Robert (The journal of dermatology, 2018)
Hand eczema (HE) is a common skin disease that impairs health-related quality of life (HRQOL). Impairments in HRQOL have already been reported in Japanese HE patients using the Skindex-16. Recently, an instrument to measure disease-specific HRQOL in HE patients was developed by an international expert group, consisting of domains for: (i) symptoms; (ii) emotions; (iii) functioning; and (iv) treatment and prevention. The objective of this study is to translate the English-language version of the Quality of Life Hand Eczema Questionnaire (QOLHEQ) to Japanese and then to validate the Japanese version. The Japanese version of the QOLHEQ, the Dermatological Life Quality Index (DLQI) and a questionnaire regarding basic demographic information, including patient ratings of HE severity, were distributed to Japanese HE patients. Additionally, a dermatologist evaluated patients' HE severity using the Physician Global Assessment. A total of 124 patients with a mean age of 43.7 years were included in the analysis, and 78% of the sample was female. Cronbach's alphas for the domains symptoms, emotions, functioning, and treatment and prevention were 0.76, 0.89, 0.88 and 0.81, respectively. The total QOLHEQ score showed a strong correlation with the DLQI, a moderate correlation with patient-rated severity and weak correlations with dermatologist-rated severity and the number of consultations. The Japanese version of the QOLHEQ showed excellent reliability and high validity. The Japanese version of the QOLHEQ is ready for use in epidemiological studies to evaluate HRQOL impairments in HE patients.